2022
DOI: 10.3390/cancers14153569
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Disorders with Predisposition to Paediatric Haematopoietic Malignancies—A Review

Abstract: The view of paediatric cancer as a genetic disease arises as genetic research develops. Germline mutations in cancer predisposition genes have been identified in about 10% of children. Paediatric cancers are characterized by heterogeneity in the types of genetic alterations that drive tumourigenesis. Interactions between germline and somatic mutations are a key determinant of cancer development. In 40% of patients, the family history does not predict the presence of inherited cancer predisposition syndromes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 124 publications
0
1
0
Order By: Relevance
“…Second-hit variants (especially deletions) in ETV6 are common in ETV6-RUNX1 rearranged leukemias [ 171 ]. In addition, somatic rearrangements with RUNX1 are observed in a quarter of ALL patients [ 172 ]. Studies using umbilical cord blood from healthy newborns have shown that ETV6-RUNX1 translocations can occur in more than 1% of the healthy population [ 173 ].…”
Section: Myeloid Neoplasms With Preexisting Platelet Disordersmentioning
confidence: 99%
“…Second-hit variants (especially deletions) in ETV6 are common in ETV6-RUNX1 rearranged leukemias [ 171 ]. In addition, somatic rearrangements with RUNX1 are observed in a quarter of ALL patients [ 172 ]. Studies using umbilical cord blood from healthy newborns have shown that ETV6-RUNX1 translocations can occur in more than 1% of the healthy population [ 173 ].…”
Section: Myeloid Neoplasms With Preexisting Platelet Disordersmentioning
confidence: 99%
“…Second-hit variants (especially deletions) in ETV6 are common in ETV6-RUNX1 rearranged leukemias [104]. In addition, somatic rearrangements with RUNX1 are observed in a quarter of ALL patients [105]. Studies using umbilical cord blood from healthy newborns have shown that ETV6-RUNX1 translocations can occur in more than 1% of the healthy population [106].…”
Section: Etv6mentioning
confidence: 99%